1998
DOI: 10.1016/s0014-5793(97)01611-6
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a heat‐stable activator protein for ADP‐ribosylation factor‐dependent phospholipase D1

Abstract: A heat-stable activator for ADP-ribosylation factor (ARF)-dependent phospholipase D (PLD) was purified to near homogeneity from rat kidney cytosol by a sequential column chromatography. The purified activator has a molecular mass of 23 kDa on SDS-PAGE. Using a partially purified ARFdependent PLD from rat kidney, the activator synergistically stimulates PLD with ARF in time-and dose-dependent manner. In the absence of ARF, the activator has little or no effect. The purified activator also stimulates PLD under s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Sci. USA 95 (1998) 12251 4) and RhoA (26), PKC (9, 10), unidentified cytosolic proteins with 50 kDa (11,12) and 23 kDa (14). PtdIns-4,5-P 2 (3) and PtdEtn (27) also are involved in the reaction, although these lipids do not serve as the substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sci. USA 95 (1998) 12251 4) and RhoA (26), PKC (9, 10), unidentified cytosolic proteins with 50 kDa (11,12) and 23 kDa (14). PtdIns-4,5-P 2 (3) and PtdEtn (27) also are involved in the reaction, although these lipids do not serve as the substrates.…”
Section: Discussionmentioning
confidence: 99%
“…The active components in the cytosol consist of at least three protein factors; ARF, RhoA, and a heat-stable protein (13). The heat-stable protein shows a molecular size of 23 kDa upon SDS͞PAGE (14). Sequence analysis now reveals that this protein is highly homologous to previously known G M2 ganglioside activator.…”
mentioning
confidence: 95%
“…Nakamura et al found from their experiment in cell free system (26) that 1.6 M AS could unmask the PLD activity from inhibitory agents in the tissue extract. Since then, they have included 1.6 M of AS in the reaction mixture to examine the rat kidney PLD activity in vitro (25)(26)(27). They, however, did not examine the effect of GM2AP in the absence of AS except on one occasion in which the PLD activity was assayed in the absence of AS using streptolysin-O-permeabilized HL-60 cells (25).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, additional activities for GM2AP have been described. a ) GM2AP enhanced the ADP-ribosylation factor-dependent phospholipase D (PLD) activity in vitro (25)(26)(27). b ) GM2AP inhibited the stimulatory activity of platelet activating factor (PAF) to release intracellular Ca 2 ϩ pools (28).…”
mentioning
confidence: 99%
“…The immunoprecipitated proteins were eluted with a FLAG peptide (100 µg\ml) and subjected to SDS\PAGE using 12.5 % gels [21] followed by immunoblot analysis [22]. In some experiments (see Figure 5 below) FLAGtagged PLD2 immunoprecipitated with anti-FLAG M2 affinity gels was incubated with the heat-treated supernatant fractions (100 µg of protein each) prepared from rat kidney [23], purified recombinant G M# activator (3 µg) or ARF (3 µg) in the presence of 5 µM PtdCho, 80 µM PtdEtn, 7 µM PtdIns(4,5)P # and 1 mM MgCl # for 2 h. The immunoprecipitated proteins were eluted from the gels and analysed as above.…”
Section: Immunoprecipitation and Immunoblot Analysesmentioning
confidence: 99%